1989
DOI: 10.1093/geront/29.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Costs of Older Persons With Cognitive Impairments

Abstract: The 1981-1982 National Long-Term Care Channeling Demonstration Project data revealed that the mean annual cost per capita for home and institutional care for cognitively impaired persons was +18,500. The equivalent figure for cognitively intact persons was +16,650. Cognitively impaired persons used nursing homes at twice the rate of cognitively intact persons. Use differences for other health services were slight. A pre- and post-nursing home admission analysis indicated that for the cognitively impaired the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…The NYC AD sample is, on the whole, older, more impoverished, and less healthy than the other Sample chosen evidently to exclude subjects with formal care, f r o m Coughlin & Liu (1989), Table 3, excludes mild/no cognitive impairment group, f r o m Weinberger et al (1993), sum from Table 3 (Adult day care category interpreted as hrs/week). Estimate from Rice et al (1993), Exhibit 1, "Social Services," valued at $9 = 1 formal hour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NYC AD sample is, on the whole, older, more impoverished, and less healthy than the other Sample chosen evidently to exclude subjects with formal care, f r o m Coughlin & Liu (1989), Table 3, excludes mild/no cognitive impairment group, f r o m Weinberger et al (1993), sum from Table 3 (Adult day care category interpreted as hrs/week). Estimate from Rice et al (1993), Exhibit 1, "Social Services," valued at $9 = 1 formal hour.…”
Section: Discussionmentioning
confidence: 99%
“…Although estimates of hourly care received by people with AD are now available (Coughlin & Liu, 1989;Ernst & Hay, 1994;Ernst, Hay, Fenn, Tinklenberg, & Yesavage, 1997;Hu, Huang, & Cartwright, 1986;Huang, Cartwright, & Hu, 1985;0stbye & Crosse, 1994;Rice et al, 1993;Souetre etal., 1995;Stommel, Collins, & Given, 1994;Weinberger et al, 1993), these have been based, for the most part, on clinic or tertiary care referral series and have mainly involved cross-sectional samples. Much less frequent are analyses using longitudinal panels (Tennstedt, Crawford, & McKinlay, 1993).…”
mentioning
confidence: 99%
“…According to estimates on the incidence and prevalence of Alzheimer's disease, net expected direct costs for these patients were projected to have been $9578 in 1983; over half involved nursing home care.5 Another report using aggregated data estimated the total direct cost of senile dementia to be $13.3 billion; of $6.4 billion in medical costs, 40%o were expended in nursing homes.6 Data from the National Long-Term Channeling Demonstration project indicated that the estimated annual cost ofcommunity care for dementia patients is $11 700, compared with $22 300 for dementia patients receiving nursing home care. 7 Although these studies provide insights into the economic burden ofdementia, they lack primary data to assess the expense of caring for dementia patients. One …”
Section: Introductionmentioning
confidence: 99%
“…An estimated two to four million Americans suffer from dementia (Coughlin & Liu, 1989). This is not to say that dementia is an inevitable result of the aging process, but it is associated with a number of conditions and diseases which increase in prevalence with increasing age.…”
Section: Introductionmentioning
confidence: 99%